Lo Kitsch en El Conejo más estúpido de este siglo: pieza dramática de Santiago Merchant. - Guerrero, Manuela E. Vera (Diálogos Latinoamericanos, 2014)
Written and directed by Santiago Merchant, The Stupidest Rabbit of This Century is a dramatic work that reflects Colombian theatre in the 21st century. This play serves as a paradigm of the historical and ideological transformation that Colombian society, and in particular Colombian theatre, is undergoing. The notion of kitsch, as developed by Matei Calinescu, exposes the irruption of modernity, but it also states certain cultural implications because what is kitsch becomes symptomatic of the industrial, capitalist society that engulfs us. Merchant treats the concept of kitsch as an intrinsic element in this play. The analysis for this article, that uses dramatology as a methodology, shows the relationship between form and content that together assemble a codified message, while proposing an interesting social critique.